KAJIAN TEORI KONSTRUKTIVIS SOSIAL DAN SCAFFOLDING DALAM PEMBELAJARAN MATEMATIKA - Yuniar Ika Putri Pranyata (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study aims to conduct a theoretical study of social constructivism and scaffolding in mathematics learning. Social constructivism is a learning approach that emphasizes collaboration and social interaction between teachers and students, as well as among students, to create understanding of mathematical concepts. Scaffolding is a supportive strategy used by teachers to assist students in understanding the material by providing appropriate assistance based on their level of comprehension. The literature review method is employed in this research to gather data from various sources relevant to social constructivism and scaffolding in mathematics learning. The study presents an in-depth overview of both theories and their application in the context of mathematics education. The findings of this research are expected to provide valuable insights for educators, curriculum developers, and stakeholders in optimizing the implementation of social constructivism and scaffolding in mathematics learning. By understanding and effectively applying these concepts, it is hoped that mathematics education can become more interactive, meaningful, and supportive of enhancing students' comprehension and academic achievement.